1994
DOI: 10.1002/ar.1092400404
|View full text |Cite
|
Sign up to set email alerts
|

Reduced surface area in apoptotic rounding of human chang liver cells from serum deprivation

Abstract: Gross surface area reduction with evidence of distinctive endocytic activity including uptake of huge 2 million mol.wt dextran particles suggested large channel endocytic internalization as a causal factor in apoptotic rounding, in common with rounding in M-phase and interphase cells with pHi upshifting where concomitant surface area reduction and uptake of impermeant particles were similarly demonstrable. The reduction in size of the cell envelope, together with consequential concentration pressures, could ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Further, at 48 h, in controls, vast cell-denuded areas could be recorded, but also areas with abundant rounding cells, still adhering onto the ECM-coated glass. This is in agreement with Sit et al [14], who show that starvation for growth factors present in serum induces apoptosis in human cultured liver cells, and with Allen et al [15], who maintain that cultivating cells in a serum-free medium induces cell death. However, in the present study, normally looking stretched cells were still plentiful in cultures as late as 48 h, exposed to AAP or AAP þ NAC or none.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Further, at 48 h, in controls, vast cell-denuded areas could be recorded, but also areas with abundant rounding cells, still adhering onto the ECM-coated glass. This is in agreement with Sit et al [14], who show that starvation for growth factors present in serum induces apoptosis in human cultured liver cells, and with Allen et al [15], who maintain that cultivating cells in a serum-free medium induces cell death. However, in the present study, normally looking stretched cells were still plentiful in cultures as late as 48 h, exposed to AAP or AAP þ NAC or none.…”
Section: Discussionsupporting
confidence: 91%
“…Serum contains growth factors. Deprivation of growth factor-containing serum from human Chang liver cells in vitro [14] has been shown to cause cell retraction and rounding up, eventually leading to apoptosis. Twenty-four hours can therefore be taken as a timepoint within the linear portion of the growth curve.…”
Section: Discussionmentioning
confidence: 99%
“…Other apoptotic systems have similarly suggested that mitotic cells are not necessarily spared from suicidal death, namely after serum deprivation of Chang liver cells (Sit et al, 1994) and micromolar staurospo-rine treatment of transformed keratinocytes (KB cells) where cells in G2/M are consistently seen to be abolished (Myint et al, 1996). Various chromosomes accumulated by treatment with colchicine or similar metaphase spindle poisons are susceptible to endonuclease digestion, producing differential bandings in cytogenetic studies (Burkholder, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometric evaluation was done in the Coulter EPICS PROFILE II using the EPICS ELITE Flow Cytometer Workstation program, version 3.0 (Coulter Electronics, Hialeah, FL). Protocol was as previously described (Sit et al, 1994(Sit et al, , 1996a. For cytological evaluation, cells from 50 µl of the cell suspension were deposited on slides by cytospinning (Cytospin, Shandon, UK).…”
Section: Propidium Iodide (Pi)-dna Bindingmentioning
confidence: 99%
“…Curved arrow points to the large gathering of prominent microvillous anchors from a much retracted apoptotic cell. Prominent microvillous anchors and endocytic vacuoles are features of cell retraction, seen in induced cell retraction of interphase cells, spontaneous retraction of mitotic cells and serum-deprivation induced apoptosis, that could contribute to rounding and substrate detachment (Sit et al, 1990(Sit et al, , 1992a(Sit et al, , 1993(Sit et al, , 1994Sit, 1996). .…”
Section: Cytological Profiles Of Mnase-treated Whole Cellsmentioning
confidence: 99%